Evaluation and Characterization of Groundnut (Arachis hypogaea L.) germplasm lines: Evaluation and Characterization of Groundnut (Arachis hypogaea L.) germplasm lines - K SRAVANTI; V RAM REDDY; K MAMATHA; M SUJATHA; M GOVERDHAN (Journal of Oilseeds Research, 2023)
In the present investigation, 100 germplasm lines were evaluated and characterized by using six yield and yield contributing traits. Three parameters viz., days to maturity (medium -48 % and late 52 %), presence or absence of flowers on the main axis (absent-20 % and presence- 80 %) and 100-kernel weight (medium-97 % and high- 3%) were found dimorphic, whereas, shelling outturn showed three states of expression viz., low (23%), medium (64 %) and high (13%). The characters of dry pod yield/plot was in the range of 159 g (ICGV 201130) to 755 g (ICGV 201174) and kernel yield/plot was in the range of 97 g (ICGV 201130) to 562 g (ICGV 201174). The genotypes were grouped based on the data and further, based on the objective, the lines will be used in the breeding programme.